Stimulating preschoolers' focus on structure in repeating and growing patterns. (August 2021) - Wijns, Nore; Verschaffel, Lieven; De Smedt, Bert; De Keyser, Laure; Torbeyns, Joke
Abstract: This study presents a patterning intervention for 5-year-olds, who were in their third year of preschool in Flanders (Belgium), with two key elements: A focus on the structure of patterns, and the inclusion of growing patterns (e.g., ABAABAAAB) in addition to repeating patterns (e.g., ABABAB). We evaluated the impact of this intervention on patterning and numerical ability in a quasi-experimental pretest-intervention-posttest design with a business-as-usual control group. The intervention consisted of a 20 week program with children in the patterning condition receiving weekly 30 min of patterning activities. After the intervention, the patterning group (n = 73) outperformed the control group (n = 74) on both repeating and growing patterns. We observed no transfer effect to children's numerical ability. Highlights: Development of a patterning intervention for 5-year-olds with two key elements. Key element 1: Stimulating insight into the underlying structure of the pattern. Key element 2: Focus on not only repeating, but also growing patterns in preschool. Intervention was effective in stimulating repeating and growing patterning ability. No differences in numerical ability between the patterning and control group.